The court of arbitration for sport jurisprudence on match-fixing: a legal update - Diaconu, Madalina; Kuwelker, Surbhi; Kuhn, André (My University, 2021)
The Court of Arbitration for Sport (CAS) jurisprudence on manipulation of sports competitions has vastly evolved from its initial award in RSC Anderlecht in 1998, to now Labuts in August 2020. Alongside, international and national regulations, as well as sporting regulations, including, most recently, the Council of Europe’s Macolin Convention on the Manipula-tion of Sports Competitions, have sought to effectively tackle the omnipresent, ever-growing phenomenon of competition manipulation. Against this backdrop, this article briefly outlines the existing legal landscape on manipulation, followed by a chronological detailing of each CAS issued award. The key aspects of defining such sanctionable behaviour, select issues of standard of proof and types of evidence which are admissible and relied on, as well as the manner and quantum of sanction are then analysed. Ultimately, noting empirical trends across these awards, questions on ne bis in idem, proportionality of sanctions and legal certainty across CAS jurisprudence are raised.
Keywords: Manipulation of sports competitions · Match-fixing · Court of arbitration for sport · Disciplinary sanctions · Evidence · Macolin convention · Ne bis in idem · Proportionality of sanctions · Legal certainty